2005
DOI: 10.1021/bi0502700
|View full text |Cite
|
Sign up to set email alerts
|

Structural Consequences of the Inhibitor-Resistant Ser130Gly Substitution in TEM β-Lactamase,

Abstract: Abstractβ-Lactamase confers resistance to penicillin-like antibiotics by hydrolyzing their β-lactam bond. To combat these enzymes, inhibitors covalently cross-linking the hydrolytic Ser70 to Ser130 were introduced. In turn, mutant β-lactamases have emerged with decreased susceptibility to these mechanism-based inhibitors. Substituting Ser130 with glycine in the inhibitor-resistant TEM (IRT) mutant TEM-76 (S130G) prevents the irreversible cross-linking step. Since the completely conserved Ser130 is thought to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
79
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(86 citation statements)
references
References 36 publications
7
79
0
Order By: Relevance
“…Lefurgy et al examined the kinetic properties of N152S and -T P99 variants with penicillin and cephalosporin substrates and concluded that hydrogen bonding of S152 or T152 to K67 or to the substrate accounted for the preservation of catalytic activity (16). They hypothesized that a water molecule can play a catalytic role in the N152G variant of P99, as has been shown for S130G SHV (25,37,38). The recently reported crystal structure of the N152G P99 variant shows considerable space left by the N152G mutation, occupied by the His 6 tag at the C terminus of the protein (39).…”
Section: Resultsmentioning
confidence: 98%
“…Lefurgy et al examined the kinetic properties of N152S and -T P99 variants with penicillin and cephalosporin substrates and concluded that hydrogen bonding of S152 or T152 to K67 or to the substrate accounted for the preservation of catalytic activity (16). They hypothesized that a water molecule can play a catalytic role in the N152G variant of P99, as has been shown for S130G SHV (25,37,38). The recently reported crystal structure of the N152G P99 variant shows considerable space left by the N152G mutation, occupied by the His 6 tag at the C terminus of the protein (39).…”
Section: Resultsmentioning
confidence: 98%
“…The latter step seems to be important for permanent inactivation of certain ␤-lactamases. Indeed, several inhibitor-resistant class A variant enzymes which bear a serine-to-glycine mutation have been described (60)(61)(62).…”
Section: Discussionmentioning
confidence: 99%
“…Amino acid substitutions in TEM and SHV result in resistance to clavulanate by two primary mechanisms: (i) alterations in the geometry of shape of the oxyanion hole and (ii) changes in the position of Ser130 or Arg244 (33,73,101,120,408,411,416). The individual residues that are most commonly substituted in IR TEM enzymes are Arg244, the nearby Asn276 and Arg275, Met69, and the active-site Ser130 (www .lahey.org/studies/webt.asp) (Fig.…”
Section: Substitutions In Class a Enzymes Conferring Inhibitor Resistmentioning
confidence: 99%
“…Removing the cross-linking residue seems a clear way to overcome inactivation, but inhibitors, and particularly tazobactam, retain efficacy against the Ser130Gly enzyme. Based on these mechanistic roles, how does the Ser130Gly variant maintain hydrolytic activity and why does it confer resistance to inhibitors (408)? In response to the first part of the question, evidence from X-ray crystallography of SHV and TEM Ser130Gly (PDB 1TDL and 1YT4, respectively) confirmed that a relocated water molecule, initially predicted by Helfand et al, compensates for the loss of the Ser130 hydroxyl group by donating a proton to the ␤-lactam nitrogen (153,157,180,408,438).…”
Section: Substitutions In Class a Enzymes Conferring Inhibitor Resistmentioning
confidence: 99%
See 1 more Smart Citation